2021
DOI: 10.1093/jrr/rrab026
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral effects of acute low-dose whole-body irradiation

Abstract: Radiation exposure has multiple effects on the brain, behavior and cognitive functions. It has been reported that high-dose (>20 Gy) radiation-induced behavior and cognitive aberration partly associated with severe tissue destruction. Low-dose (<3 Gy) exposure can occur in radiological disasters and cerebral endovascular treatment. However, only a few reports analyzed behavior and cognitive functions after low-dose irradiation. This study was undertaken to assess the relationship between brain ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Both galactic cosmic radiation and solar particle events comprise primarily moderate-to-high energy protons, which are largely sparsely ionizing ( Townsend et al, 2006 ). Terrestrial radiation sources that are sparsely ionizing include higher-energy photons produced by X-ray generators and linear accelerators, as well as gamma rays produced by sources such as 137 Cs or 60 Co. Whole-body photon irradiation at moderate doses and a high dose rate (1 and 3 Gy; dose rate of 0.69 Gy/min) induces behavioral alterations, including increased measures of anxiety and cognitive injury, and reduces dopamine and GABA levels in 6–8-week-old C57BL6/J male mice 7 days after exposure ( Bekal et al, 2021 ). Post-fear learning photon irradiation (4 Gy; dose rate: 1.25 Gy/min) impairs the extinction of contextual and cued fear memory of 1-month-old C57BL/6J male mice 2 weeks after exposure ( Olsen et al, 2014 ) and enhances cued fear memory of 3-month-old C57BL/6J mice ( Olsen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both galactic cosmic radiation and solar particle events comprise primarily moderate-to-high energy protons, which are largely sparsely ionizing ( Townsend et al, 2006 ). Terrestrial radiation sources that are sparsely ionizing include higher-energy photons produced by X-ray generators and linear accelerators, as well as gamma rays produced by sources such as 137 Cs or 60 Co. Whole-body photon irradiation at moderate doses and a high dose rate (1 and 3 Gy; dose rate of 0.69 Gy/min) induces behavioral alterations, including increased measures of anxiety and cognitive injury, and reduces dopamine and GABA levels in 6–8-week-old C57BL6/J male mice 7 days after exposure ( Bekal et al, 2021 ). Post-fear learning photon irradiation (4 Gy; dose rate: 1.25 Gy/min) impairs the extinction of contextual and cued fear memory of 1-month-old C57BL/6J male mice 2 weeks after exposure ( Olsen et al, 2014 ) and enhances cued fear memory of 3-month-old C57BL/6J mice ( Olsen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The range of radiation doses in the present study was expanded to include 3, 8, and 10 Gy. The 3-Gy dose was selected as previous studies have shown that behavioral performance can be affected at this low dose ( Bekal et al, 2021 ). In addition, we analyzed the plasma collected 9 months after sham irradiation or total body irradiation for distinct alterations in metabolic pathways and to determine whether changes to metabolic measures were associated with specific behavioral and cognitive measures.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of newly diagnosed cancer patients receive radiotherapy, and 60% with curative intent [1]. Radiation exposure to the brain has a diverse impact on behavior and cognitive functions in a time and dose-dependent manner [2]. Pelvic radiotherapy is applied to treat cancers in the pelvic region, including genitourinary, gynecologic, anorectal origin, and localized prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The whole-body irradiation of mice (0.5 Gy, 1 Gy and 3 Gy ionizing radiation) provokes alteration in normal behavior over 10 days. Serotonin levels have undergone changes in the blood, hippocampus, and whole brain tissue [ 9 ], and cognitive impairment has been observed. Kokhan et al reported an effect on the protein content of 5-HT 2A and 5-HT 4 receptors in the prefrontal cortex, as well as a decreased content of serotonin transporter and increased content of tryptophan hydroxylase in the hypothalamus of irradiated rats [ 10 ].…”
Section: Introductionmentioning
confidence: 99%